2016
DOI: 10.4067/s0717-95022016000200047
|View full text |Cite
|
Sign up to set email alerts
|

Alteraciones Morfológicas en Dientes Sometidos a Altas Temperaturas con Interés Forense

Abstract: SIOLI, J. M.; SANTOS, I.; FONSECA, G. M. & MARTIN-DE-LAS-HERAS, S.Alteraciones morfológicas en dientes sometidos a altas temperaturas con interés forense. Int. J. Morphol., 34(2):719-728, 2016. RESUMEN:Los dientes son los elementos más resistentes del esqueleto humano y son utilizados en muchas ocasiones en la rutina de los laboratorios forenses. El objetivo de este estudio fue describir los cambios dentarios estructurales, morfológicos y del color que se producen tras la incineración, para ayudar en el manejo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(48 reference statements)
0
4
0
2
Order By: Relevance
“…To our best knowledge, this is the first time that the color of cortical and medullar areas have been spectrophotometric measured in heated bones. Spectrophotometric techniques avoid the subjectivity of color shade comparisons and utilize a white standard as reference with the same measurement conditions, and reproducibility of results has been successfully tested [23,24]. The main advantage of our study is that color measurement is performed directly on the bones, with no intermediate steps between sample and color measurements [22].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…To our best knowledge, this is the first time that the color of cortical and medullar areas have been spectrophotometric measured in heated bones. Spectrophotometric techniques avoid the subjectivity of color shade comparisons and utilize a white standard as reference with the same measurement conditions, and reproducibility of results has been successfully tested [23,24]. The main advantage of our study is that color measurement is performed directly on the bones, with no intermediate steps between sample and color measurements [22].…”
Section: Discussionmentioning
confidence: 95%
“…In a previous study, we have demonstrated how spectrophotometer analysis could be used to estimate the temperature of exposure with high accuracy in heated human teeth [23,24]. In this research, we propose to estimate the temperature based on color changes in medullar and cortical fresh human bone zones accurately measured with a digital spectrophotometer.…”
Section: Introductionmentioning
confidence: 99%
“…Los dientes son las estructuras más resistentes del cuerpo humano al calor, pueden soportar temperaturas de hasta 1600 °C sin pérdida importante de su microestructura, por lo que permanecen casi intactos mucho tiempo después de que los tejidos blandos y esqueléticos se han destruido por incineración (Rubio, Sioli, Santos, Fonseca & Martin-de-las-Heras, 2016).…”
Section: Comportamiento De Tejidos Dentales Y Materiales Odontológicos Bajo La Acción De Altas Temperaturasunclassified
“…Lo importante de los resultados que arrojan estos estudios es comprobar que tanto los dientes como los materiales empleados en la práctica odontológica presentan alta resistencia a las altas temperaturas, lo que posibilita conocer la identidad de individuos quemados, carbonizados o incinerados a través de sus dientes y tratamientos odontológicos efectuados (Rubio, Sioli, Santos, Fonseca & Martin-de-las-Heras, 2016).…”
Section: Comportamiento De Tejidos Dentales Y Materiales Odontológicos Bajo La Acción De Altas Temperaturasunclassified
“…Metric sex estimation of burned skeletal remains can basically be achieved in four different ways. First, a shrinkage correction factor may be used according to the extent of heat-induced change which is usually predicted by resorting to the interpretation of chromatic changes since these are approximately correlated to the maximum temperature at which bones have been subjected to [3,5,21,22,23,24]. For example, Buikstra and Swegle [25] proposed a 10% shrinkage correction factor for calcined bones.…”
mentioning
confidence: 99%